(untitled) (GAIMS Journal of Medical Sciences, 2023)
Giardia lamblia (also known as Giardia intestinalis and Giardia duodenalis) is the most frequent intestinal parasite responsible for chronic diarrhea and malnutrition. Giardia infections commonly cause nausea, abdominal cramping, bloating, and foul-smelling diarrhea in patients. Usually, Giardiasis causes a self-limiting illness, but it can progress to a severe disease in immunocompromised individuals and cause dehydration, malnutrition, and failure to thrive. As a result, early diagnosis and treatment are required to control the infection and prevent complications. Infectious Disease Society of America diagnostic guidelines recommend obtaining stool studies to diagnose Giardiasis. When stool tests are negative, but suspicion persists, a duodenal biopsy is a gold standard for diagnosis. We present the case of a patient diagnosed with Giardia by an incidental duodenal biopsy specimen obtained during a workup for malnutrition and chronic diarrhea, despite a normal stool examination. A few cases of Giardiasis have been diagnosed and reported in the literature using a duodenal biopsy. Some studies addressed the same issue, and we believe that duodenal biopsy can be a good strategy for diagnosing Giardiasis with high sensitivity and specificity.